REVEALING JAVANESE TRADITIONAL ORCHESTRA SONGS MEANING DURING THE VILLAGE PURIFYING RITUAL 'NYADRAN' - Afandi, Titah (Jurusan Sastra Indonesia, 2024)
Indonesia, as a multicultural country, has many indigenous cultures; one of those cultures is the village purifying ritual usually held by Javanese society. This study investigates the relationship between the Javanese traditional orchestra songs meaning and the village purifying ritual in Sonoageng Village, Nganjuk Regency. This study employs the descriptive qualitative method with a narratological approach. The results show a relationship between the implicit meaning of analyzed gendhing and the village purifying ritual.